DEVELOPMENT OF INTERACTIVE E-BOOK BASED ON CHEMICAL REPRESENTATION ON ELECTROLYSIS CELL TOPIC - Ila Rosilawati; Duwi Wulandari; M Setyarini (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Development of Interactive E-Book Based on Chemical Representation on Electrolysis Cell Topic. This research was aimed to develop an interactive e-book and describe its characteristics and validity as well as to describe the teachers’ and students’ responses of interactive e-book was developed. The research design used Borg and Gall method of research and development which only carried out until the fifth stage, namely the revision stage of the trial results. The data obtained were analyzed using descriptive statistical analysis. Characteristics of interactive e-book based on chemical representation of the electrolysis cell topic was developed, starting with discourses related to everyday life phenomena accompanied by pictures based on chemical representation, equipped with identification columns, explanation columns, observation tables and interactive questions. The results of expert validation on the aspects of content suitability, construction and readability all have very high criteria. Based on this, the interactive   e-book based on the chemical representation on electrolysis cell topic is said to be valid. In addition, the results of the teacher's responses to aspects of the suitability of content, construction and readability as well as the results of student responses to aspects of attractiveness and readability each have very high criteria.                                                                Keywords: interactive e-book, chemical representation, electrolytic cell